STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SEKOLAH DASAR LUGHATUNA - Deni Ansyah (UNISAN JURNAL, 2024)
Leadership is one of the determining factors in improving the quality of teacher professionalism and the success of education in schools. Without a manager or leader in an educational institution, the educational process will experience very serious difficulties, and can even result in failure in education. The aim of this research is to find out how the leadership management of Sekolah heads improves teacher professional competence. This research method uses qualitative-descriptive. Choosing this method will make it easier to understand the data presented because it is arranged accurately and systematically. This data collection uses: Observation, Interviews, and Documentation. The results or findings that can be presented in this research are several leadership management functions of Sekolah principals that are applied to achieve targets that have been set jointly by all school components, namely leadership management of Sekolah principals in increasing teacher professionalism competency by: a) Formulating Sekolah principal policies carried out using a planning process through identifying the need for sources of policy thinking, such as new ideas originating from the results of deliberations, discussions and meeting forums, implementing policies, and conducting policy evaluations. b) Organizing the head of the Sekolah in forming a committee and unity of teachers to produce the goals of a Sekolah program. c) Arrangements for the work procedures of the head of Sekolah Aliiyah are carried out by dividing students' tasks according to the existing school organizational structure. d) Supervision of the head of Sekolah Aliiyah is carried out directly on teachers and students by monitoring the activities of students and teachers by monitoring each class. e) Religious spiritual education of the head of the Sekolah in coaching and providing teachers to focus on goals and objectives